2015
DOI: 10.1007/s12010-015-1746-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Application of Biosurfactant Produced by Bacillus licheniformis R2

Abstract: The biosurfactant produced by Bacillus licheniformis R2 was characterized and studied for enhancing the heavy crude oil recovery at 80 °C in coreflood experiments. The strain was found to be nonpathogenic and produced biosurfactant, reducing the surface tension of medium from 70 to 28 mN/m with 1.1 g/l yield. The biosurfactant was quite stable during exposure to elevated temperatures (85 °C for 90 days), high salinity (10 % NaCl), and a wide range of pH (5-12) for 10 days. It was characterized as lipopeptide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 31 publications
5
39
0
Order By: Relevance
“…IFT and ST reduction are reported to have an important effect on light or heavy crude oil recovery by bacterial biosurfactants under laboratory experiments of core-flood or sand-pack column studies (Al-Sulaimani et al 2012;Joshi and Desai 2013;Joshi et al 2015). In this study, there was no much reduction in ST and IFT between treated samples and controls were observed, and only minor reduction in ST from day 17 and day 21 was observed.…”
Section: Discussionmentioning
confidence: 42%
“…IFT and ST reduction are reported to have an important effect on light or heavy crude oil recovery by bacterial biosurfactants under laboratory experiments of core-flood or sand-pack column studies (Al-Sulaimani et al 2012;Joshi and Desai 2013;Joshi et al 2015). In this study, there was no much reduction in ST and IFT between treated samples and controls were observed, and only minor reduction in ST from day 17 and day 21 was observed.…”
Section: Discussionmentioning
confidence: 42%
“…The mass spectra ( Figure 4B ) revealed the major group of peaks at m/z values between 1000 and 1090 (The mass spectra of remaining bands are as Supplementary Figure S1). This group could be attributed to the different variants of surfactins or lichenysins, as previously described (Pereira et al, 2013; Al-Wahaibi et al, 2014; Joshi et al, 2015). The HPTLC–ESI–MS is quite easy and quick technique to identify the biosurfactants.…”
Section: Resultsmentioning
confidence: 54%
“…Considering the molecular mass of different homologs of lichenysin (C 12 –C 16 ), these peaks were identified as protonated ions [M + H] + m/z 1049.1; sodium adduct ions [M + Na] + with m/z of 1015.5, 1029.5, 1043.5, and 1057.6; sodium adducts [M-H + 2Na] + with m/z of 1051.5, 1065.5, and 1079.5; potassium adducts [M + K] + with m/z of 1087.5. MALDI-TOF analysis of W16 biosurfactant showed similarity with lichenysin-A, produced by B. licheniformis strains (Grangemard et al, 1999; Mikkola et al, 2000; Li et al, 2008; Zhang et al, 2014; Joshi et al, 2015). They have reported that lichenysin – A is a cyclic heptalipopeptide having a small peptide (Gln, Leu, Leu, Val, Asp, Leu, and Ile) linked to 3-hydroxy fatty acid residue with amide (Gln) and lactone (Ile) bonds forming a cyclic structure, with main fatty acids are 3-hydroxylated tri, tetra, penta, and hexadecanoic acids.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…JF-2, was reported by Thomas et al (1993). Joshi et al (2015) reported additional 37.1 % of heavy oil from Berea sandstone cores at 80°C was achieved using a lipopeptide-type of biosurfactant. Previous studies reported that biosurfactants could potentially be used in conjunction with synthetic surfactants to provide more cost-effective enhanced oil recovery and subsurface remediation (Youssef et al 2007a, b).…”
Section: Coreflood Experiments Using Chemical Surfactant and Biosurfamentioning
confidence: 92%